Kesulitan Berbicara Siswa Sekolah Dasar dalam Pembelajaran Bahasa Inggris - Agus Rofii (Jurnal Elementaria Edukasia, 2023)
The primary skill that shows language ability is the ability to speak English. On the other hand, most students have difficulty speaking. Therefore, this research aims to find the problems students experience when learning English, especially regarding speaking skills. English speaking skills are increasingly important in the current era of globalization. However, students in elementary school often need help with speaking English well. A crucial first step to overcoming English learning problems in elementary schools is understanding and analyzing the difficulties students face in speaking skills. Elementary school students in one of the Majalengka areas need help speaking English. One of them is the need to have greater self-confidence when speaking. Language and psychological factors can influence students' difficulties when speaking English. This research uses qualitative research using observations and interviews in elementary schools. Based on the results of the analysis, it can be concluded that five factors are responsible for students' difficulties in speaking English. They include lack of vocabulary, poor pronunciation and pronunciation, lack of friends or peers to talk to, lack of self-confidence, and class atmosphere. This research found that building students' self-confidence and providing organized activities is essential, especially in elementary schools.